2021
DOI: 10.3390/ijms22094352
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinases: Modulators of Different Types of Regulated Cell Death

Abstract: The mechanisms and physiological implications of regulated cell death (RCD) have been extensively studied. Among the regulatory mechanisms of RCD, ubiquitination and deubiquitination enable post-translational regulation of signaling by modulating substrate degradation and signal transduction. Deubiquitinases (DUBs) are involved in diverse molecular pathways of RCD. Some DUBs modulate multiple modalities of RCD by regulating various substrates and are powerful regulators of cell fate. However, the therapeutic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 232 publications
(312 reference statements)
0
7
0
Order By: Relevance
“…2b ), suggesting a potential primary role for the ubiquitin-dependent degradation pathway in GPX4 reduction. The ubiquitin-proteasome system (UPS) and deubiquitinating enzymes (DUBs) are critical for cellular protein homeostasis, executing both post-transcriptional degradation and stabilization 18 . They also play a crucial role in ferroptosis and kidney disease pathology 10 , 19 .…”
Section: Resultsmentioning
confidence: 99%
“…2b ), suggesting a potential primary role for the ubiquitin-dependent degradation pathway in GPX4 reduction. The ubiquitin-proteasome system (UPS) and deubiquitinating enzymes (DUBs) are critical for cellular protein homeostasis, executing both post-transcriptional degradation and stabilization 18 . They also play a crucial role in ferroptosis and kidney disease pathology 10 , 19 .…”
Section: Resultsmentioning
confidence: 99%
“…This was performed to investigate the anticancer mechanism of functionalized AuNPs and correlate the critical end points finding (cytotoxicity, ROS, MMP) with that of DUB protein expression. Several studies have shown that targeting DUBs might be an effective approach in cancer therapy due to their significant role in controlling cellular mechanisms such as apoptosis, cell proliferation, DNA transcription and repair, cell cycle progression, immune response, and protein modification. In this study, the protein expression of DUBs in cancerous A549 and noncancerous MRC-5 lung fibroblast cells without AuNP treatment was first analyzed. It was found that proteins were upregulated in A549 cells compared to MRC-5 which correlated with the proliferation of A549 cells being cancerous cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous study reported that K128E of Bax has the potential to alter the release of cytochrome c, and the point mutations of Bax prevent apoptosis-inducing functions [ 46 ]. The importance of the role of DUBs has been emphasized, and it is known that DUB functions in apoptosis and aging-related diseases, including neurodegenerative diseases [ 47 , 48 ]. Research on these DUBs should therefore continue for cancers or neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%